The Effect of Using Directed Reading Thinking Activity (DRTA) Strategy on the Tenth Grade Students' Reading Comprehension Achievement at MA Unggulan Nuris Jember - Hayu Novendiana, Frida; Tasnim, Zakiyah; Arya Wijaputra, Bambang (Jurnal Edukasi, 2016)
The aim of this research was to know whether or not there was a significant effect of using Directed Reading Thinking Activity (DRTA) strategy on the tenth grade students at MA Unggulan Nuris Jember. The research design used was quasi experimental research specifically post test only non equivalent group design . The respondent of the research was chosen by using cluster random sampling by a lottery . The students of X IPA A as the experimental group and X PK B as the control group. The data was collected by interview, documentation and administering reading comprehension test. Then the data collected were analyzed by using independentt sample T-test . It was known that the mean score of the experimental group was 78.80 and the mean score of the control group was 73.73. In the output of the t-test column, it was shown that the significant value was 0.03. It was lower than 0.05. It means that the mean scores of the two classes (experimental and control groups) were different. Therefore, there was a difference between the experimental class and the control class. In conclusion, the use of Directed Reading Thinking Activity (DRTA) strategy was a significantly affected on the tenthgrade students’ reading comprehension achievement tat MA Unggulan Nuris Jember. Keywords: reading comprehension achivement, DRTA strategy